Reposicionamento de beta amino cetonas em ensaios in silico e in vitro de atividade antimalárica e antitumoral - Krombauer, Gabriela Camila (2020)
Drug repositioning has being on evidence in the process of drug discovery and optimization due to the agility, cost-benefit and safety of the process, which consists in the using a drug that is alredy in the market for another disease. Based on the current need for new drugs and the problems regarding drug resistence, our study aimed to evaluate in silico 10 beta amino ketones for antimalarial potential activity; the same compoucnd were evaluate for antitumoral potencital activity in vitro. Our in silico results showed that all 10 compounds bonded with at least six therapeutic targets of Plasmodium falciparum, including protein complesxes and ezymes such as Plasmodium falciparum glutaredoxin-like proteins (4N0Z); P. falciparum Ferredoxin-NADP+ reductase (2OK8); P. falciparum ATPase calcium pump ortholog (PfATP6); Plasmodium falciparum Triosephosphate Isomerase−Phosphoglycolate Complex (1LYX); crystal structure of PfPK7 in complex with an ATP analogue (2PML); the hexose transporter of Plasmodium falciparum (PfHT); all of them responsible for its physiological functions. Regarding the antimalarial activity, the compound 3- (morpholin-4-yl) -1- phenylpropan-1-one (AB1) showed an IC50 of 0.98 µM and selectivity index greater than 60; for the antitumor activity, AB1 showed promising results in the treatment of breast adenocarcinoma cell lines (line MDA-MB-231), verified by the antitumor potential and induction of cell death through colorimetric assay based on Caspase-3. The physical-chemical properties of compound AB1 are compatible with the absorption, distribution, metabolism and excretion criteria established by the Lipinski rule, therefore, demonstrate its potential as a drug prototype for antimalarial and antitumor activity.